Towards the development of a mycoinsecticide to control white grubs (Coleoptera: Scarabaeidae) in South African sugarcane - Goble, Tarryn Anne (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2013)
In the KwaZulu-Natal (KZN) Midlands North region of South Africa, the importance and increased prevalence of endemic scarabaeids, particularly Hypopholis sommeri Burmeister and Schizonycha affinis Boheman (Coleoptera: Melolonthinae), as soil pests of sugarcane, and a need for their control was established. The development of a mycoinsecticide offers an environmentally friendly alternative to chemical insecticides. The identification of a diversity of white grub species, in two Scarabaeidae subfamilies, representing seven genera were collected in sugarcane as a pest complex. Hypopholis sommeri and S. affinis were the most prevalent species. The increased seasonal abundances, diversity and highly aggregated nature of these scarabaeid species in summer months, suggested that targeting and control strategies for these pests should be considered in this season. Increased rainfall, relative humidity and soil temperatures were linked to the increased occurrence of scarab adults and neonate grubs. Beauveria brongniartii (Saccardo) Petch epizootics were recorded at two sites in the KZN Midlands North on H. sommeri. Seventeen different fluorescently-labelled microsatellite PCR primers were used to target 78 isolates of Beauveria sp. DNA. Microsatellite data resolved two distinct clusters of Beauveria isolates which represented the Beauveria bassiana senso stricto (Balsamo) Vuillemin and B. brongniartii species groups. These groupings were supported by two gene regions, the nuclear ribosomal Internal Transcribed Spacer (ITS) and the nuclear B locus (Bloc) gene of which 23 exemplar Beauveria isolates were represented and sequenced. When microsatellite data were analysed, 26 haplotypes among 58 isolates of B. brongniartii were distinguished. Relatively low levels of genetic diversity were detected in B. brongniartii and isolates were shown to be closely related. There was no genetic differentiation between the two sites, Harden Heights and Canema in the KZN Midlands North. High gene flow from swarming H. sommeri beetles is the proposed mechanism for this lack of genetic differentiation between populations. Microsatellite analyses also showed that B. brongniartii conidia were being cycled from arboreal to subterranean habitats in the environment by H. sommeri beetles. This was the first record of this species of fungus causing epizootics on the larvae and adults of H. sommeri in South Africa. The virulence of 21 isolates of Beauveria brongniartii and two isolates of B. bassiana were evaluated against the adults and larvae of S. affinis and the adults of H. sommeri and Tenebrio molitor Linnaeus (Coleoptera: Tenebrionidae). Despite being closely-related, B. brongniartii isolates varied significantly in their virulence towards different hosts and highlighted the host specific nature of B. brongniartii towards S. affinis when compared to B. bassiana. Adults of S. affinis were significantly more susceptible to B. brongniartii isolates than the second (L2) or third instar (L3) grubs. The median lethal time (LTâ‚…â‚€) of the most virulent B. brongniartii isolate (C13) against S. affinis adults was 7.8 days and probit analysis estimated a median lethal concentration (LCâ‚…â‚€) of 4.4Ã—10â · conidia/mlâ »Â¹. When L2 grubs were treated with a concentration of 1.0Ã—10â ¸ conidia/mlâ »Â¹, B. brongniartii isolates HHWG1, HHB39A and C17 caused mortality in L2 grubs within 18.4-19.8 days (LTâ‚…â‚€). Beauveria brongniartii isolate HHWG1 was tested against the L3 grubs of S. affinis at four different concentrations. At the lowest concentration (1Ã—10â ¶ conidia/mlâ »Â¹), the LTâ‚…â‚€ was 25.8 days, and at the highest concentration (1Ã—10â ¹ conidia/mlâ »Â¹) the LTâ‚…â‚€ dropped to 15.1 days. The persistence of B. bassiana isolate 4222 formulated on rice and wheat bran and buried at eight field sites in the KZN Midlands North was evaluated by plating out a suspension of treated soil onto a selective medium. All eight field sites showed a significant decline in B. bassiana CFUs per gram of soil over time, with few conidia still present in the samples after a year. Greater declines in CFUs were observed at some sites but there were no significant differences observed in the persistence of conidia formulated on rice or wheat bran as carriers. Overall, poor persistence of B. bassiana isolate 4222 was attributed to suboptimum temperatures, rainfall, which rapidly degraded the nutritive carriers, attenuated fungal genotype and the action of antagonistic soil microbes. Growers' perceptions of white grubs as pests and the feasibility of a mycoinsecticide market were evaluated by means of a semi-structured questionnaire. The study showed that the reduced feasibility of application, general lack of potential demand for a product, high cost factors and most importantly, the lack of pest perception, were factors which would negatively affect the adoption of a granular mycoinsecticide. Growers however exhibited a positive attitude towards mycoinsecticides, and showed all the relevant attributes for successful technology adoption. It is recommended that because B. brongniartii epizootics were recorded on target pests which indicated good host specificity, dispersal ability and persistence of the fungus in the intended environment of application; that a mycoinsecticide based on this fungal species be developed. What will likely increase adoption and success of a mycoinsecticide is collaboration between various industries partners to increases market potential in other crops such as Acacia mearnsii De Wild (Fabales: Fabaceae).
Keywords: Insecticides -- Environmental aspects Insecticides -- Toxicology Beetles -- South Africa -- KwaZulu-Natal Beetles -- Control -- South Africa -- KwaZulu-Natal Coleophoridae -- South Africa -- KwaZulu-Natal Scarabaeidae -- South Africa -- KwaZulu-Natal Sugarcane -- Diseases and pests -- South Africa -- KwaZulu-Natal Sugarcane -- Diseases and pests -- Control -- South Africa -- KwaZulu-Natal; Insecticides